PENERAPAN MEDIA DIGITAL INTERAKTIF DALAM MENINGKATKAN KEMAMPUAN MEMBACA BAHASA ARAB - Rabiatun Adawiah; Yahfizham Yahfizham (Jurnal Recoms, 2025)
This study aims to determine the effectiveness of implementing interactive digital media in improving Arabic reading skills among secondary-level students. The background of this research stems from the observed low interest and comprehension of students when engaging with Arabic texts, which often poses challenges in the language learning process. To address this issue, the study utilized interactive digital media such as Android-based learning applications, interactive quizzes, and educational animations which are believed to offer a more engaging, communicative, and student-centered learning environment. This research employed a quantitative method using a pretest-posttest design, involving two groups: an experimental group that used interactive digital media and a control group that relied on conventional teaching methods. Data were collected through standardized reading comprehension tests administered before and after the intervention. The findings revealed a statistically significant improvement in Arabic reading skills among students in the experimental group compared to those in the control group. The results support the hypothesis that interactive digital media can enhance students' motivation, attention, and understanding of Arabic texts. Therefore, it can be concluded that the integration of digital technology in language instruction provides an effective alternative to traditional methods, especially in increasing reading proficiency in Arabic among secondary school students.